Planeación Financiera en American Boutique de la ciudad de Loja, período 2016-2020 - Tandazo Solano, Herenia Beatríz (2017)
The thesis work entitled "FINANCIAL PLANNING IN AMERICAN BOUTIQUE OF THE CITY OF SHOP, PERIOD 2016-2020" has as general objective to realize a planning that allows to know the profits that will have in the future allowing its manager proprietor to make the best decisions for Economic and financial improvement. The methodology that was used to develop the thesis work is the percentage increment that allowed to elaborate the forecasts of sale and purchase for the predicted years, determining the entrances and exits of the merchandise, being May, June, July and October the months that more Purchases made, to meet the needs of customers in subsequent months despite the fact that their sales are low damaging the liquidity of the same, to elaborate the cash budgets took into account the different policies maintained by the company, the same as Allowed to know the inflows and outflows of cash as well as determine in which month the company will have a deficit or know if there is cash in it, Determining that in the months of July, August and October the company will need financing due to the fact that its purchases are not evenly distributed, which does not reflect much concern because the rest of the month its revenues increase and it has sufficient liquidity; Finally, the pro forma financial statements were prepared, which allowed us to forecast the different financial economic situations that the company will obtain over the budgeted periods, thus determining the 5 financial capacity and liquidity that the company will have to meet with its short and medium term obligations. Finally, the most relevant conclusions of the thesis work are presented so that the owner manager considers them as an option for an appropriate decision making process that helps the progress and development of the business